Beyond memory: exploring the value of social cognition for older adults with neurocognitive disorders - Samtani, Suraj; Meka, Anjani; Siette, Joyce (Frontiers in Psychiatry, 2023)
Neurocognitive disorders involves progressive decline in cognition, function, behavior and needs. Recent developments have identified the need to characterize social cognition in individuals with neurocognitive impairments to support uncertainty in clinical decision making, treatment plans and monitoring individual change. Routine social cognition assessments have thus been more recently used and adopted in persons with dementia or mild cognitive impairment. This work serves to summarize current assessments and provide a discourse on the practicality of available social cognition tools, its implication in clinical practice and key future directions. We highlight the need to establish validated, multicomponent measures of social cognition for people with neurocognitive disorders.